(The Feeling of) Meaning-as-Information. (May 2014) - Heintzelman, Samantha J.; King, Laura A.
The desire for meaning is recognized as a central human motive. Yet, knowing that people want meaning does not explain its function. What adaptive problem does this experience solve? Drawing on the feelings-as-information hypothesis, we propose that the feeling of meaning provides information about the presence of reliable patterns and coherence in the environment, information that is not provided by affect. We review research demonstrating that manipulations of stimulus coherence influence subjective reports of meaning in life but not affect. We demonstrate that manipulations that foster an associative mindset enhance meaning. The meaning-as-information perspective embeds meaning in a network of foundational functions including associative learning, perception, cognition, and neural processing. This approach challenges assumptions about meaning, including its motivational appeal, the roles of expectancies and novelty in this experience, and the notion that meaning is inherently constructed. Implications for constructed meaning and existential meanings are discussed.